Presentation of meta-analysis plots. (March 2015) - Wald, NJ; Bestwick, JP
Meta-analysis (forest) plots are widely used to show the results from multiple individual randomized trials or observational studies that address the same question, including the assessment of screening markers. They show the between study spread of results and provide a summary estimate of the results from all the studies combined. We here illustrate the advantage of ordering study results by the magnitude of the effect and including a vertical shaded band encompassing the summary 95% confidence interval of the summary estimate to emphasize the uncertainty of the estimate in a way that is more prominent than only displaying a "diamond" around its value.